Noninvasive high-intensity focused ultrasound for skin brightening efficacy using a topical agent containing glutathione and hyaluronic acid - Kyu-Ho Yi; Eunjae Kim; Jovian Wan; Angela Wai Kay Lee; Yu-Chieh Yang; Sophie Pei-Hsuan Lu; Jeff Huang; Po Han Patrick Huang; Hsien Li Peter Peng (Journal of Dermatological Treatment)
Background High-intensity focused ultrasound (HIFU) is well-documented for skin rejuvenation, lifting, and tightening. However, its synergistic effects with topical agents, enhanced by HIFU-induced vibration and heat, remain underexplored.Objective To evaluate clinical and photographic outcomes of HIFU combined with a topical agent versus the topical agent alone.Method This non-randomized controlled trial involved 20 female volunteers (ages 30–55) divided into two groups. Group A (n = 10) received two HIFU sessions combined with a topical agent containing glutathione and hyaluronic acid. Group B (n = 10) received the topical agent alone. Outcomes were assessed using digital photography, patient satisfaction surveys, and the A-One Smart™ system for fine wrinkles, hyperpigmentation, and hydration. Skin brightening was evaluated with the Global Esthetic Improvement Scale (GAIS).Results Group A showed significant reductions in fine wrinkles (6.25 ± 2.00 mm to 3.10 ± 1.62 mm), improved hyperpigmentation (3.50 ± 0.80 to 2.10 ± 1.05), and increased hydration (28 ± 10 to 55 ± 11) (all p < 0.05). Over two-thirds of Group A reported significant improvements, with no complications. Group B showed minimal, non-significant changes (p > 0.05), with only 30% reporting noticeable improvements.Conclusion Combining HIFU with a topical agent significantly enhances skin quality and brightness without adverse effects.